Development of Comics Physics Education with STEM for Stimulating Straight Line Motion Concept Mastery in Junior High School Students. - Niswatul Khoiriyah; Abdurrahman Abdurrahman; Agus Suyatna (Jurnal Pembelajaran Fisika, 2019)
One of the lessons that can be used to stimulate mastery of concepts is learning approach STEM. This is effective if it is supported by teaching materials in the form of physics comics. It has been done validity test which are consists of design expert test and material expert test, and the product is valid as to be used. The attractiveness, convenience, and benefit test is conducted by students and the results of attractiveness were obtained by 3.38, convenience with a score of 3.38 and benefit test were obtained 3.31. This research was conducted using one group pre post design. The results of the paired sample t test. Sig value. (2-Tailed) is less than 0.05 which is 0,000, so it can be explained related to the significant use of STEM, on the ability to master students’ concepts. Based on the value of N-gain, the average N-gain of concept mastery ability is 0.43 with the medium category.Salah satu pendekatan pembelajaran yang dapat digunakan untuk menstimulasi penguasaan konsep adalah pendekatan pembelajaran STEM. Hal tersebut efektif jika didukung dengan bahan ajar berupa komik fisika. Telah dilakukan uji validasi yang terdiri dari uji ahli desain serta uji ahli materi dan produk dinyatakan valid serta layak digunakan. Uji kemenarikan, kemudahan, dan kemanfaatan dilakukan oleh siswa dan diperoleh hasil kemenarikan dengan 3,38, kemudahan dengan skor 3,38 dan kemanfaatan 3,31. Penelitian ini dilakukan menggunakan one group pre post design. Hasil dari uji nilai paired sample t. nilai Sig. (2-Tailed) kurang dari 0,05 yaitu 0,000, maka dapat dinyatakan terdapat pengaruh yang signifikan penggunaan komik fisika berbasis STEM, terhadap kemampuan penguasaan konsep siswa. Berdasarkan nilai N-gain, rata-rata N-gain kemampuan penguasaan konsep diperoleh sebesar 0,43 dengan kategori sedang.Kata kunci: Komik Fisika, STEM, Penguasaan konsep.Kata kunci: Komik Fisika, STEM, Penguasaan konsep.